Characterization of Social Neuroticism in the Context of Intrapersonal Conflict - Petrosyan, Rafik (ՀՀ ԳԱԱ)
The article studies the phenomenon of social neuroticism in the context of intrapersonal conflict. The theoretical and conceptual characteristics of intrapersonal conflict are discussed, and the intrapersonal characteristics that are characteristic of social neuroticism are highlighted. A comparative analysis of the literature shows that intrapersonal conflicts can manifest themselves in different areas of a person’s life. They find their expression in both the cognitive, emotional, and behavioral spheres of a person. They can be manifested by a decrease in self-esteem, negative experiences, impaired activity, a decrease in the degree of general adaptability, and other indicators. The article presents the fundamentals of representatives of various psychological directions on the phenomena under discussion, as well as modern scientific interpretations of social neuroticism and intrapersonal conflict. The gender and age characteristics of the perception of intrapersonal conflict are highlighted, including social neuroticism characteristics, and methodological tools for reducing the negative impact of social neuroticism on a person’s activities have been identified. Հոդվածում ուսումն ասիրվում է սոցիալական նևրոտիզմի ֆենոմենը ներանձնային կոնֆլիկտի համատեքստում: Քննարկվել են ներանձնային կոնֆլիկտի տեսական, հայեցակարգային բնութագրումն երը, դրանցում առանձնացվել են սոցիալական նևրոտիզմին նշաններով ներանձնային հատկանիշները: Գրականության համեմատական վերլուծությունը ցույց է տալիս, որ ներանձնային կոնֆլիկտները կարող են դրևսորվել անձի կյանքի տարբեր ոլորտներում: Դրանք իրենց արտահայտումն են գտնում թե՛ անձի իմացական, թե՛ հուզական և թե՛ վարքային ոլորտներում: Դրանք կարող են դրսևորվել ինքնագնահատակի անկման, բացասական ապրումն երի, գործունեության խաթարման, ընդհանուր ադապտիվության աստիճանի նվազման ևայլ ցուցիչներով: Հոդվածում ներկայացվել են հոգեբանական տարբեր ուղղությունների ներկայացուցիչների հիմն ադրույթները քննարկվող երևույթների վերաբերյալ, ինչպես նաև սոցիալական նևրոտիզմի և ներանձնային կոնֆլիկտի ժամանակակից գիտական մեկնությունները: Առանձնացվել են ներանձնային կոնֆլիկտի ընկալման սեռային, տարիքային առանձնահատկությունները, դրանցում՝ սոցիալական նևրոտիզմի հատկանիշները, վեր են հանվել անձի գործունեության ընթացքում սոցիալական նևրոտիզմի բացասական ազդեցությունը նվազեցնելու մեթոդական գործիքները:
Keywords: Psychology